Caught Up Between War, Localism and EU Land Policy Regulations. Unravelling Local Land Use Decision-Making in Ukraine - Oleksandr Anisimov; Yegor Vlasenko; Dominic Stead; Maria Smirnova (European Journal of Spatial Development)
In global discussions on land use amid increasing land scarcity, municipal-level decision-making remains underexplored despite municipalities playing a crucial role in regulating land competition. This gap is particularly notable in supranational policies aimed at  reducing land consumption which do not account for the diversity of conditions at the municipal level. This article addresses land use decision-making in Ukraine, where pre-existing pressures on land are intensified by the impacts of war and rising demands for land conservation and reduction of land take. Using a new analytical framework, we investigate the relationship between land use  pressures, local authorities' perspectives, and policy responses at the municipal level. Focusing on the case of Vinnytsia municipality, we examine current land use measures, supplemented by a Q-methodology study to capture municipal perceptions of prospective land use and the role of municipalities in governing the land. By combining these methods, we explore how three distinct perspectives held by municipal stakeholders inform local policy actions and assess their responsiveness to both current and emerging pressures. The  findings highlight that municipalities are often unaware of their long-term role in achieving sustainable land use and further suffer  from localism and ineffective multi-level governance arrangements. This points to the need for a more grounded and context-sensitive  approach in supranational land use goals and regulations.